Pengembangan Aplikasi Survei Kredit Berbasis Android - Achmad Rizki Raharjo; Herman Tolle; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
This Android-based credit survey application is a mobile application designed to conduct surveys for customers who will apply for credit. The problem currently faced is that it is still using a manual survey process, so the survey data collection process takes longer. The purpose of making this credit survey application is to simplify and speed up the collection of survey data, so that survey data can be evaluated more quickly. The method used in making this credit survey application uses the prototyping development method. Application programming using java programming with Android studio IDE software, then for the database using PHP and mySQL. The result from making this application is that the application can display customers who will be surveyed, then retrieve survey data and send data to be stored in the database.